Facile Synthesis of Oxazolidinones as Potential Antibacterial Agents - Secret P. Els; Kimberleigh B. Govender; Mxolisi K. Sokhela; Nilay Bhatt; Nakita Reddy; Hendrik G. Kruger; Per I. Arvidsson; Hendra Gunosewoyo; Thavendran Govender; Tricia Naicker (ChemistryOpen)
Abstract An efficient microwave‐assisted synthesis route for novel oxazolidinone analogues has been developed. The general synthesis of these compounds began with an L‐proline‐mediated three‐component Mannich reaction between commercially available 3‐fluoro‐4‐morpholinoaniline, aqueous formaldehyde and α‐hydroxyacetone. This was followed by a one‐step cyclisation to form the core structure of oxazolidinone antibiotics which was subsequently derivatized. The novel compounds were evaluated for their antibacterial activity against M. smegmatis. One of the novel oxazolidinone derivatives 18 a1 produced a MIC of 8 mg/L, comparable with the commercial Rifampicin. The methodology is a useful addition to the field since it can make highly sought‐after oxazolidinone derivatives, using cheaper, less harsh commercially available reagents, in a short time and one pot.